PERAN KEPEMIMPINAN YANG MELAYANI DAN KARAKTERISTIK PEKERJAAN DALAM MEMPENGARUHI KINERJA KARYAWAN PADA PT NIAGA BUNGA CREATIVE - Qusaeri, Muammar Afif Al; Khasbulloh, M. Wahab; Wiliyanto, Wiliyanto; Khasanah, Muthi’atul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of servant leadership and job characteristics on employee performance at PT Niaga Bunga Creative. The research employed a quantitative associative approach, with data collected through questionnaires. The population consisted of 80 permanent employees, all of whom were selected as the sample using a saturated sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that both servant leadership and job characteristics have a positive and significant effect on employee performance, both partially and simultaneously. The Adjusted R Square value of 0.605 indicates that 60.5% of the variation in employee performance can be explained by the two independent variables. These findings highlight the importance of a service-oriented leadership style and well-designed job characteristics in enhancing employee productivity within the creative industry sector.